Does party colour matter? The effect of government partisanship on pledges’ left–right location - Belchior, A. M. (2024)
Despite extensive research on the ‘politics matter’ hypothesis, the findings achieved so far remain ambiguous. Inspired by that hypothesis, this research focuses on electoral promises, a chief but as yet untested indicator. It examines whether government party colour explains the adoption of an ideologically committed policy agenda in electoral manifestos. To answer this goal the research looks at the left–right placement of manifesto pledges of the Portuguese governing parties between 1995 and 2019. The results indicate that partisanship significantly explains the executive’s party agenda-setting and that this relationship prevails over time. Findings also suggest that the partisan effect is mediated by issue salience.